2011
DOI: 10.1186/1743-7075-8-66
|View full text |Cite
|
Sign up to set email alerts
|

Exercise prior to a freely requested meal modifies pre and postprandial glucose profile, substrate oxidation and sympathovagal balance

Abstract: BackgroundThe effects of exercise on glucose and metabolic events preceding and following a freely initiated meal have never been assessed. Moreover, the relationship between these events and sympathovagal balance is not known. The objective of this study was to determine whether exercise prior to a freely requested meal modifies the pre- and postprandial glucose profile, substrate oxidation and sympathovagal balance.MethodsNine young active male subjects consumed a standard breakfast (2298 ± 357 kJ). After 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 67 publications
2
12
0
Order By: Relevance
“…A more vigorous postprandial exercise has been reported to transiently increase blood glucose values compared to pre-exercise [52]. In contrast, Charlot et al [37] reported that 75 min of high-intensity cycling, compared to rest, yield sustained lower glycemia throughout the exercise session and may also exert an influence on the following meal, delaying peak postlunch glycemia with no significant difference in total glucose AUCs. However, the generalizability and practical relevance of such results may need further investigation.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…A more vigorous postprandial exercise has been reported to transiently increase blood glucose values compared to pre-exercise [52]. In contrast, Charlot et al [37] reported that 75 min of high-intensity cycling, compared to rest, yield sustained lower glycemia throughout the exercise session and may also exert an influence on the following meal, delaying peak postlunch glycemia with no significant difference in total glucose AUCs. However, the generalizability and practical relevance of such results may need further investigation.…”
Section: Resultsmentioning
confidence: 98%
“…The remaining 18 studies investigated the effect of exercise on postprandial events, modulating some parameters related to meals and exercise (i.e. exercise intensity and duration, meal size and composition) [36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53]. …”
Section: Resultsmentioning
confidence: 99%
“…Whereas exercise training lasting for weeks or months was shown to have no impact on HRV [27], cause an increase in HRV [26,28], or lead to decreased LF and increased HF [29]. Moreover, the change in LF/ HF ratio after exercise also varied: some found that it shifted to a sympathetic dominance [25], some reported a parasympathetic activation [30], or that there was no significant change [28]. Populationbased studies have shown that leisure time physical activity of greater intensity is associated with higher levels of LF and HF [31].…”
Section: Discussionmentioning
confidence: 99%
“…Although HRV is an established method to assess autonomic innervation of the heart, the effects of exercise on HRV vary widely. Moderate exercise was reported to cause a reduction in the high-frequency component (HF) [23], in both the HF and lowfrequency component (LF) [25], in HRV as a whole [26], or no significant change in HF [2]. Whereas exercise training lasting for weeks or months was shown to have no impact on HRV [27], cause an increase in HRV [26,28], or lead to decreased LF and increased HF [29].…”
Section: Discussionmentioning
confidence: 99%
“…The end of the exercise occurred 120 min after the completion of breakfast and was designated t120. According to our previously described procedure (Charlot et al 2011), the participant was then placed in an isolated room deprived of time cues (no computer, smartphone, or watch) and had to spontaneously request his lunch by pressing the button of a visual alarm when he felt the need to eat.…”
Section: Study Design and Proceduresmentioning
confidence: 99%